ANALISIS PENGARUH SIKAP, KONTROL PERILAKU, DAN NORMA SUBJEKTIF TERHADAP PERILAKU SAFETY - Gilang Dwi Prakoso; Mohammad Zainal Fatah (Universitas Airlangga, 2017)
Safety behavior in the workplace has aims to make the workers get off from work accidents that can cause financial or material losses, disability and death. The workers supposed to work safety so that companies or workplaces get the financial or material benefits. The purpose of this research was to find out the factors that affect workers to work safety. This research was an analytical descriptive with quantitative approach. Data collection was using questionnaires to respondents. The worker’s safety behavior which difficult to control when working made the number of workplace accident bigger. To know the factors that influence safety behavior was by connecting attitude, subjective norm, and worker’s perceived with safety behavior according to company rules. The results of this study showed that there was a relationship between attitude, perceived, and subjective norm with the worker’s safety behavior. This is showed by the use of PPE such as helmet, shoes, and earplug. The important of safety behavior for the worker was to alert the worker of their safety and security when they were working so they not got financial and material loss for the company, disability and death of the workers.Keyword: safety, perceived, subjective norm and attitude